ANTS AS POTENTIAL VECTORS OF PATHOGENS IN HOSPITALS IN THE STATE OF SAO-PAULO, BRAZIL - Fowler, H. G.; Bueno, O. C.; Sadatsune, T.; Montelli, A. C. (Icipe Science Press, 1993)
Baiting studies performed in large, medium and small hospitals in Brazil revealed the presence of 14 ant species, with up to nine recorded in one hospital. Dominant species were exotic ants, and in the large hospital, Tapinoma melanocephalum was the most prevalent. Ants were not uniformly spread through the hospitals, but tended to be found in the more critical areas, particularly in nursery, intensive care, obstetrics, neurology and dermatology units. Bacteriological studies using specific media for bacteria associated with intra-hospital infections indicated the potential for the mechanical vectoring of species of Staphylococcus, Serratia, Klebsiella, Acinetobacter, Enterobacter, Candida and Enterococcus by ants. Although T. melanocephalum did not have the highest rate of association with these bacteria, its ubiquitous occurrences resulted in the highest overall potential as a vector of these bacteria. Because of a large number of ant species occurring in Brazilian hospitals, ants pose a potential problem to the spread of diseases in hospitals. Because of the number of associated ant species in hospitals, the control of this potential problem is much more difficult than in registered temperate areas.
Keywords: ANTS; VECTORS; INTRAHOSPITAL INFECTION; BACTERIA; BRAZIL; TAPINOMA-MELANOCEPHALUM